PEMBERDAYAAN KARANG TARUNA “TUNAS HARAPAN” MELALUI PELATIHAN KEWIRAUSAHAAN UNTUK MENCIPTAKAN JIWA ENTERPRENEURSHIP DI DESA CIHERANG KECAMATAN GUNUNGSARI SERANG BANTEN - Listiawati Listiawati; Ende Ende; Sigit Auliana (LPPM Universitas Bina Bangsa, 2024)
The place for this novice community service activity was carried out in Ciherang Village, Gunungsari District, Serang Regency. The target audience is members of the Tunas Harapan Youth Organization. The problems faced by Karang Taruna Tunas Harapan are: activities cannot run well because human resources, business capital and marketing collide. The purpose of this activity is to increase the knowledge and skills of Karang Taruna Tunas Harapan members in running a business by utilizing the potential of agricultural and plantation products in Ciherang Village, so that an entrepreneurial spirit can be created. The results of this service activity can motivate youth members to become entrepreneurs by utilizing the potential of agricultural and plantation products, by implementing business management and information technology